How to Choose the Best Treatment Strategy for Graves’ disease – Cooperation Between Doctor and Patient - Kula, Paula; Haber, Mateusz; Czachor, Adrianna; Kucy, Natalia; Kotula, Alicja; Grelewicz, Olga; Servaas, Elwira; Juśkiewicz, Adam; Siemiątkowski, Robert (Quality in Sport, 2024)
Graves’ disease (GD) is an autoimmune thyroid disease characterized by hyperthyroidism, enlarged thyroid gland, and ophthalmopathy. It is the most common cause of hyperthyroidism, especially in middle-aged women. The pathological mechanism involves the production of antibodies against the TSH receptor (TRAbs), which leads to uncontrolled stimulation of the thyroid gland and excessive production of thyroid hormones. This study examined optimal treatment strategies for Graves’ disease, emphasizing the critical role of physician-patient collaboration. The paper discusses the clinical aspects of Graves’ disease, focusing on the recurrent nature of the disease with periods of exacerbations and remissions. Additionally, attention is drawn to the commonly associated disease: orbitopathy, which may lead to permanent damage to the orbital tissues, eye movement disorders, deterioration of visual acuity, and even blindness. The paper presents current therapeutic approaches, including pharmacotherapy, radioactive iodine treatment and surgical interventions. It emphasizes the importance of personalized treatment plans and the need for regular monitoring to minimize the risk of complications. This study emphasizes active patient involvement in treatment decisions to determine the most effective treatment strategy for Graves’ disease, improving patient outcomes and quality of life.